PENYULUHAN TENTANG PHBS, TOGA, DAN SWAMEDIKASI KEPADA MASYARAKAT RW. 006, KELURAHAN KETAPANG, KECAMATAN CIPONDOH, KOTA TANGERANG - Hurit, Hermanus Ehe; Eden, Yonathan; Purnomo, Antonius Dewanto; Ayuni, Dewi Sartika; Limas, Ayu; Surjana, Vernant; Anantya, Catur; Salsabilla, Ersa; Azzuhra, Hanifah Nur; Atilah, Niken Tri Rachmah (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Ketapang is an urban village located in Cipondoh sub-district, Tangerang City, Banten, Indonesia. This urban village consists of 11 RW (Rukun Warga) and 70 RT (Rukun Tetangga). RW. 006 is located in Ketapang urban village and consists of 1029 family cards. The problems found in RW 006 includes the poor waste disposal system, the lack of understanding and application of hand washing according to the Hand Washing with Soap (CTPS) procedure, the poor processing of Family Medicinal Plants (TOGA) which have been widely planted in the RW. 006 environment, and the lack of interest of residents to see a doctor or other health facilities. The number of self- medication behaviors also makes DAGUSIBU (Get, Use, Store, and Dispose) of medicine an important thing to socialize. The method used is to conduct socialization and practical education directly to the community. The results obtained were changes in public awareness to dispose of waste according to its type (organic and non-organic). An increase in the percentage of CTPS socialization participants who can wash their hands according to CTPS from 20% to 100%; an increase in the percentage of socialization participants' knowledge related to TOGA processing from 52% of respondents to 99.33%; and an increase in the percentage of correct answers to DAGUSIBU socialization participants from 39% of respondents to 82.33% also showed that the PFS activities carried out succeeded in providing positive changes in community knowledge in the RW 006 environment. Socialization related to self-medication has the potential to change the mindset of the RW 006 community about the importance of seeing a doctor, but does not guarantee changes in the behavior patterns/habits of the community who are more likely to do self-care